Psycho-social challenges faced by children living in the streets: case study of Mutare - Chinyai, Delight (Midlands State University, 2017)
The research seeks to bring out the psycho-social challenges that are faced by children living in the streets of Mutare. The study was anchored on the notion that children living in the streets are human beings that should enjoy their lives just like any other children. However, in Zimbabwe and other countries this is not the case as some of them are facing various psycho-social challenges such as lack of shelter, poor sanitation, substance abuse, depression, discrimination and mental health problems. Children living in the streets are often homeless, hungry and abused, and some measures need to be implemented in order to help street children.. The research used the qualitative research method because it puts emphasis on the natural setting and the point of views of the research participants. In-depth interviews were used for data collection and the study purposively identified 12 key participants of children living in the streets. Thematic analysis was used in conducting data analysis in which it focused on identifying recurring patterns, analysing and reporting patterns (themes) of behaviour. Findings were that street children face various socioeconomic challenges, psychological challenges and low levels of self-esteem and health related issues. The study established that in the face of these challenges children living in the streets engage coping strategies that range from begging for survival, shoe shinning and car washing to earn a living, they also rely on social support from the church, government and non-governmental organisations. The study concluded that children living in the streets do face challenges hence it came up with some recommendations that will help curb the psychosocial challenges faced by children living in the streets.